Strategies for Evaluating BIPA Learning in Islamic Religious Higher Education Institutions - Elin Nailur Rahmah (Khazanah Multidisiplin, 2025)
This study evaluates the strategies for teaching Bahasa Indonesia for Foreign Speakers (BIPA) in Islamic religious higher education institutions, focusing on their effectiveness, challenges, and implementation success rates. The study was conducted through observations at the Language Center of UIN Bandung, interviews with stakeholders, and analysis of program evaluation results. Findings indicate that competency-based strategies, such as pre-tests and post-tests, are effective in enhancing foreign students' language skills, particularly in speaking, listening, reading, and writing. Additionally, the BIPA program successfully strengthened students' understanding of religious values and local culture. However, challenges include differences in students' linguistic backgrounds, limited learning tools, and difficulties integrating learning materials with cultural and religious contexts. The study concludes that the evaluation strategies applied have shown significant results, although curriculum adaptation and technology-based approaches are needed to improve efficiency. This research provides valuable contributions to the development of more effective BIPA programs in Islamic religious higher education institutions to support intercultural dialogue and global integration.